Some remarks on the Khasi language (Atti del Sodalizio Glottologico Milanese, 2014)
Khasi is an Austro-Asiatic language spoken mainly in Meghālaya. It differs in many respects from the general type of Indian languages, most of which share important areal traits, thus forming a linguistic area. Khasi is an SVO language, at least in its standard dialect. It possesses a set of articles (identical with third person personal pronouns), which do not mark definiteness but such features as gender, number and size/endearment. In connection with this, Khasi also exhibits interesting agreement phenomena. KEYWORDS: Khasi, Austro-Asiatic language family, word order, Sprachbund, articles